2022
DOI: 10.3389/fphar.2022.835991
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pharmacological interventions for pruritus in primary biliary cholangitis: A systematic review and meta-analysis

Abstract: Background and objective: Pruritus is a common complication in patients with primary biliary cholangitis (PBC). The pathogenesis is not clear, and also the precise therapeutic measures remain alluring. In order to systematically evaluate the efficacy and safety of drug interventions in the treatment of pruritus associated with PBC, this systemic review and meta-analysis was conducted.Methods: The randomized controlled trials (RCTs) on drug interventions in the treatment of pruritus associated with primary chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…For patients suffering from both PBC and psoriasis, interdisciplinary collaboration among medical professionals is essential for timely diagnosis and optimal treatment. A systematic review and meta-analysis published in 2022 identified several medications effective in alleviating PBC-related pruritus ( 24 ), including ursodeoxycholic acid (UDCA), methotrexate (MTX), and GSK2330672, an intestinal bile acid transporter inhibitor. These drugs significantly reduced pruritus scores or provided pruritus relief.…”
Section: Discussionmentioning
confidence: 99%
“…For patients suffering from both PBC and psoriasis, interdisciplinary collaboration among medical professionals is essential for timely diagnosis and optimal treatment. A systematic review and meta-analysis published in 2022 identified several medications effective in alleviating PBC-related pruritus ( 24 ), including ursodeoxycholic acid (UDCA), methotrexate (MTX), and GSK2330672, an intestinal bile acid transporter inhibitor. These drugs significantly reduced pruritus scores or provided pruritus relief.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a UDCA dose within the range of 8–15 mg/kg/day has been used effectively to treat primary biliary cholangitis or gallstones [ 41 , 42 ]. In this work, we used equivalent doses to those used in humans, efficiently reducing gallstones, cholestasis, and intestinal inflammation in other mice models [ 43 46 ].…”
Section: Discussionmentioning
confidence: 99%